Prosody takes over: Towards a prosodically guided dialog system - Nöth, Elmar; Kießling, Andreas; Niemann, Heinrich; Ott, Karin; Batliner, Anton; Mast, Marion; Kuhn, Thomas; Kompe, Ralf (Speech Communication, 1994)
The domain of the speech recognition and dialog system EVAR is train time table inquiry. We observed that in real human-human dialogs when the officer transmits the information, the customer very often interrupts. Many of these interruptions are just repetitions of the time of day given by the officer. The functional role of these interruptions is often determined by prosodic cues only. An important result of experiments where naive persons used the EVAR system is that it is hard to follow the train connection given via speech synthesis. In this case it is even more important than in human-human dialogs that the user has the opportunity to interact during the answer phase. Therefore we extended the dialog module to allow the user to repeat the time of day and we added a prosody module guiding the continuation of the dialog by analyzing the intonation contour of this utterance.
Keywords: DIALOG; SENTENCE MODALITY; PROSODY; SPEECH UNDERSTANDING